Komitmen organisasi pegawai puskesmas: Integrasi karakteristik individu, karakteristik pekerjaan, pengalaman kerja, dan kualitas kehidupan kerja - Raka Zildjian; Hermin Endratno; Akhmad Darmawan; Arini Hidayah (Journal of Management and Digital Business, 2026)
This study is based on the increasing tasks and responsibilities of employees at Kemranjen I and II Community Health Centers, particularly in the service and data management sectors in Kemranjen District. The objective of this research is to analyze the influence of individual, job, and work experience characteristics on organizational commitment. This study employs a quantitative method, with data collection conducted through questionnaires and observations. The population consists of 121 employees, and the sampling technique used is total sampling, whereby the entire population serves as the sample. The analysis is performed using the Partial Least Squares (PLS) approach with a Structural Equation Modeling (SEM) framework. The results indicate that individual characteristics, job characteristics, work experience, and quality of work life each have a positive and significant effect on organizational commitment. Affective Events Theory explains how internal and external factors trigger positive emotions, thereby strengthening employees' emotional attachment, so it is recommended to optimize these factors to increase organizational commitment.